“Efecto de los promotores de crecimiento en el cultivo de Maracuyá (Passiflora edulis f. flavicarpa) en Ecuador” - Bustamante Loor, Jorge Enrique (2022)
The effect of growth promoters in the cultivation of passion fruit (Passiflora edulis f. flavicarpa) in Ecuador, determined that growth promoters in passion fruit nursery plants affect the agronomic characteristics for transplanting to the final site in each of the variables. : number of leaves, plant height, stem diameter and leaf area. The cultivation of passion fruit requires adequate amounts of amino acids, macro and micro nutrients that must be available for the plants to develop and produce satisfactorily, since the plant absorbs them throughout the year, when the soil fails to meet these needs it is It is necessary to supplement these nutrients at the most appropriate time, being the periods of flowering and fruit formation in which the consumption of nutrients is more intense. The use of biostimulant substances and/or growth promoters generate positive effects on the variables number of leaves, root length and dry weight of the root part. Applications of T. harzianum as a growth promoter were able to stimulate growth in both the aerial and root parts. In Ecuador, passion fruit is one of the fruits with the greatest international projection, since in recent years the demand has increased with an upward trend and it ranks as the third largest exporter in South America after Brazil and Colombia. It has been reported that in recent years, the country has exported passion fruit both in fresh fruit, as well as in pulp, juice and concentrate.